Role of Company's Efficiency Measure in achieving return: Iraq's Private Banks Case - AL Abdullah, Mohammed Jasim Mohammed; Alyaseen, Ahmed Abd Alkareem Mohammed; Faez Hasan, Mohammed (Technium Social Sciences Journal, 2023)
Measures, especially efficiency measures, are crucial and pivotal in determining a company's performance level and financial health, as well as the extent to which they are reflected in other indicators. This study investigates the extent to which the company’s efficiency measure (working capital) contributes to achieving returns for the period 2009-2018. Therefore, it assumes that the efficiency measure (working capital) does not contribute to achieving the cumulative abnormal return. This study drew several findings, the most crucial of which is the rejection of the hypothesis of the study and the acceptance of the alternative hypotheses, which can be summed up as the efficiency measure (working capital) contributing to achieving the cumulative abnormal return. The study has concluded a set of recommendations, including the need to raise awareness of working capital as a major contributor to achieving a distinct type of stock returns.